Reconstruction of Law Enforcement in Indonesia Through Strengthening the Embodiment of PancasilaValues of Justice to Realize Humane Law Enforcement - Fajar Bima Alfian (Pancasila and Law Review)
Globalization has significantly impacted various sectors, including law enforcement in Indonesia, bringing both positive and negative consequences. Current law enforcement practices have often lacked a solid foundation, resulting in persistent injustices. Consequently, there is a need for both preventive and curative measures to enhance the realization of justice based on Pancasila, particularly within the prosecutor's office. This paper employs a normative juridical research method, incorporating philosophical, conceptual, and case approaches. The findings indicate that law enforcement must integrate the noble values of Pancasila with the principles of restorative justice to shape and frame existing policies. This integration aims to create a justice system that fosters fairness for perpetrators, victims, and the public, addressing judicial issues and promoting humane practices within the prosecutorial system. Furthermore, Pancasila’s values should be ingrained in law enforcers, including prosecutors, to ensure that their role contributes to a more equitable legal system. While judges adjudicate cases with the principle of "For the Sake of God Almighty," the prosecutor's office must also play a critical role in advancing fairer law enforcement in Indonesia.